Quality Components of the Tourist Industry and Development of a Toolkit for their Integrated Assessment - Baiev, Vadim; Bakhov, Ivan; Antonenko, Irina; Sologub, Yuriy; Veres, Kateryna (My University, 2018)
According to the World Tourism Organization, the average pace of tourism development is 2-2 times higher than the average annual growth rate of national economies as a whole. For many countries, foreign, that is inbound, tourism turned into a primary or, at least, significant source of export income. In the current context of increased competition and globalization of business when the producer market is replaced by the consumer market it is especially important for tourism organizations to ensure competitiveness of their services. It largely depends on quality of services themselves but quality determined by consumer demand. In this connection, the issue of introducing of a toolkit for integrated assessment of quality components of the tourist industry takes on particular significance. The paper examines the main components of the tourist industry quality that characterize the ability of a country’s tourist industry to render quality tourist services. It identifies the structural components of the tourist industry quality index and quality index calculation methods as a set of the infrastructure and resources quality sub-index, multi-purpose tourist product consumer satisfaction sub-index, and safety security sub-index.
Keywords: tourist industry; quality index; infrastructure quality; consumer satisfaction Sub-Index; and Safety &Security Sub-Index; кафедра туристичного та готельного бізнесу